If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18x + -8 = 4(3x + -3) + 6x + 4 Reorder the terms: -8 + 18x = 4(3x + -3) + 6x + 4 Reorder the terms: -8 + 18x = 4(-3 + 3x) + 6x + 4 -8 + 18x = (-3 * 4 + 3x * 4) + 6x + 4 -8 + 18x = (-12 + 12x) + 6x + 4 Reorder the terms: -8 + 18x = -12 + 4 + 12x + 6x Combine like terms: -12 + 4 = -8 -8 + 18x = -8 + 12x + 6x Combine like terms: 12x + 6x = 18x -8 + 18x = -8 + 18x Add '8' to each side of the equation. -8 + 8 + 18x = -8 + 8 + 18x Combine like terms: -8 + 8 = 0 0 + 18x = -8 + 8 + 18x 18x = -8 + 8 + 18x Combine like terms: -8 + 8 = 0 18x = 0 + 18x 18x = 18x Add '-18x' to each side of the equation. 18x + -18x = 18x + -18x Combine like terms: 18x + -18x = 0 0 = 18x + -18x Combine like terms: 18x + -18x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| -10=-14v+10v | | 400-.03x=X | | 6x-2(4x-5)=46 | | -4(w-6)+7=-33 | | x-0.7=1.6 | | Y-5/2=1/2 | | 3(6+7n)=102 | | 5(3x+5)=12 | | -7(-2-2x)=-84 | | 2(3x+4x)=14 | | 194=6(5n+4)+4n | | X-08/8/9=6/7 | | -2(4t-4)+5t=6t-9 | | -5(-4-2m)=90 | | -4(3y-2)-y=-3(y-3) | | gh2j/s | | 9x+0.3=63.3 | | -6-13=4x+14-3x | | 7(2-z)/6=-2 | | -4(1+6p)=-100 | | 46=-3d+7 | | 6.99+0.55=11.94 | | y+3.3=-9.4-6.5 | | -7(3x-2)+6=-21x+20 | | 129=3(-7n+8) | | 3lne^3x=0 | | 5x+19=2(2x+8) | | 22+x=41 | | 18x-7(5-3x)=-87 | | -8x-7////95-3x)=-87 | | 100=33x+Y | | 33=9r-3 |